Factors Associated With Marshallese and Hispanic Adults' Willingness to Receive a COVID-19 Booster Dose - Rachel S. Purvis; Jennifer L. Vincenzo; Marissa Spear; Ramey Moore; Susan K. Patton; Jennifer Callaghan-Koru; Pearl A. McElfish; Geoffrey M. Curran (SAGE Publishing, 2023)
Introduction/Objectives: New variants of the SARS-CoV-2 virus that causes COVID-19 will continue to develop and spread globally. The Omicron variant identified in November 2021 has many lineages. Variants spread quickly and can infect previously vaccinated individuals, prompting the Centers for Disease Control and Prevention to update vaccination recommendations. While ~230 million Americans received the initially-recommended vaccine sequence, booster uptake has been much lower; less than half of fully vaccinated individuals report receiving a booster. Racial disparities also mark patterns of COVID-19 vaccination booster uptake. This study explored willingness and motivations to get a COVID-19 booster among a diverse sample of participants. Methods: We used convenience sampling to recruit participants 18 years of age or older who attended a community vaccine event. We conducted informal interviews during the recommended 15-min post-vaccination wait time with 55 participants who attended vaccine events at Marshallese and Hispanic community locations and comprised the recruitment pool for individual interviews. Using a qualitative descriptive design, we conducted in-depth follow-up interviews with 9 participants (Marshallese n = 5, Hispanic n = 4) to explore willingness and motivations to get boosted. We used rapid thematic template analysis to review informal interview summaries and formal interviews. The research team resolved data discrepancies by consensus. Results: Participants reported high willingness to get boosted, especially if boosters were recommended in the future to protect against serious illness and mitigate the spread of COVID-19. This finding underscores how essential including recommendations to get a COVID-19 booster from trusted sources in health messaging and educational campaigns may be for increasing booster uptake. Participants described their preference for receiving future COVID-19 boosters, reporting that they would attend similar vaccine events, especially those held at faith-based organizations and facilitated by the same community partners, community health workers, and research staff. This finding shows how community engagement can overcome barriers to vaccination (ie, transportation, language, and fear of discrimination) by providing services in preferred community locations with trusted community partners. Conclusions: Findings document high willingness to get a COVID-19 booster, emphasize the role of recommendations from trusted sources in motivating booster uptake, and highlight the importance of community engagement to address disparities in vaccination coverage and reach.